Masalah Administrasi dan Manajemen Sekolah - Rahmilawati Ritonga; Yesica Nainggolan; Enjel Ika; Febry Nurhayati Sagala; Shanaz Mayla Nissa (Politeknik Kampar, 2025)
This study aims to identify and analyze the main problems in school administration and management, especially related to student data management, organizational systems, and documentation and reporting. Using the literature review method, this study summarizes findings from various sources related to the obstacles faced by schools, such as poorly structured student data management, the absence of an integrated organizational system, untimely documentation and reporting, and difficulties in dealing with change and lack of innovation in teaching methods. The proposed solutions include the use of information technology to modernize the administration system, improve coordination and communication between departments, and develop systematic work procedures and professional training for education personnel. The results of the study are expected to provide a comprehensive picture of the challenges of school administration and offer strategic recommendations to improve the quality of education services through more effective and efficient administrative governance